Concretes with synthetic aggregates for sustainability. (15th February 2017) - Tekin, Ilker; Yasin Durgun, Muhammed; Gencel, Osman; Bilir, Turhan; Brostow, Witold; Hagg Lobland, Haley E.
Graphical abstract: Variations in ultrasound pulse velocity for different concretes according to age. The trend in compressive strength behavior of the concretes is similar. Abstract: We have used waste marble aggregates, marble dust and fly ash from thermic power plants as fillers in concretes for replacing natural aggregates. We have used two different kinds of cements. After curing, we have determined the workability (by slump tests), air content, unit weight, Schmidt hardness, ultrasound pulse velocity, compressive strength and carbonation depth. The concretes containing waste marble at least match or exceed the workability and strength of the control concrete type. Fly ash significantly improves the workability. Utilizing waste marble aggregate at the replacement ratio of 100% along with waste marble dust, fly ash and pozzolanic cements in concrete leads to lower cost – achieving at the same time environmentally friendly production process with decreased consumption of natural resources and energy. Our work also contributes to enhancement of sustainability by finding a use for marble waste and fly ash.